Establishment of MDR1-knockout human induced pluripotent stem cell line. Issue 3 (June 2020) - Negoro, Ryosuke; Kawai, Kanae; Ichikawa, Moe; Deguchi, Sayaka; Takayama, Kazuo; Mizuguchi, Hiroyuki
Abstract: Multiple drug resistance 1 (MDR1) is highly expressed in various organs, including the liver, small intestine, and blood–brain barrier (BBB). Because MDR1 plays important roles in the excretion of many drugs, it is necessary to evaluate whether drug candidates are potential substrates of MDR1. Recently, many researchers have shown that human induced pluripotent stem (iPS) cell-derived differentiated cells such as hepatocytes and enterocytes can be applied for pharmacokinetic testing. Here, we attempted to generate MDR1-knockout (KO) iPS cell lines using genome editing technology. The correctly targeted human iPS cell lines were successfully obtained. The expression levels of pluripotent markers in human iPS cells were not changed by MDR1 knockout. The gene expression levels of hepatic markers in MDR1-KO iPS-derived hepatocyte-like cells were higher than those in undifferentiated MDR1-KO iPS cells, suggesting that MDR1-KO iPS cells have hepatic differentiation capacity. In addition, MDR1 expression levels were hardly detected in MDR1-KO iPS cell–derived hepatocyte-like cells. We thus succeeded in establishing MDR1-KO iPS cell lines that could be utilized for pharmacokinetic testing. Graphical abstract: Image 1